Spolecné odborné stanovisko Sekce sportovní kardiologie Ceské asociace preventivní kardiologie CKS a Sekce sportovní kardiologie Ceské spolecnosti telovýchovného lékarství - Tuka, V.; Sovová, E.; Godula, B. J.; Jiravský, O.; Kubuš, P. (Cor et Vasa, 2020)
Elite and competitive athletes are not spared from the risk of COVID-19 infection Sports medicine physicians, general practitioners, and cardiologists may be asked about the athlete's return to sport after COVID-19 Globally, several guidelines have emerged that generally take a more cautious approach to resuming training and intense physical activity The following recommendations seek to summarize current views on the return to sports for athletes and provide guidance for the assessing physician.